Deceptive counterfeit risk in global supply chains - Ghadge, Abhijeet; Duck, Andrew; Erc, Merve; Caldwell, Nigel (Taylor & Francis, 2021)
The study investigates deceptive counterfeits in the global supply chains. It explores perceived sources of counterfeits, their impact and identifies risk mitigation strategies in Business-to-Business procurement. An online survey was used to collect data from 140 procurement professionals targeted at a national purchasing body and affiliated UK purchasing groups. The study findings show that counterfeit breaches are increasing, especially in low-cost spare parts, sourced from tier-two suppliers based in developing countries. Counterfeits lead to high costs, delays, lost sales, product recalls and even legal action. Network transparency, cost of quality and pre-supply evaluation approaches and supplier relationship management are the most effective mitigation strategies to overcome deceptive counterfeit risk in global supply chains. The study contributes to supply chain academics and practitioners’ growing research interest in counterfeit risk.
Keywords: procurement; supply chain risk management; global supply chains; Counterfeit risk